Modeling and simulation of torque hysteresis controller for brushless DC motor drives - Bahari, Norhazilina; Jidin , Auzani; Abdullah, Abdul Rahim; Othman, Md Nazri; Manap, Mustafa (2012)
This paper presents modeling and simulation of a torque hysteresis controller for brushless DC motors. Brushless DC (BLDC) motors can offer great advantageous compared to other machines used in industrial applications due to its compactness, high torque density, simpler controller and lower maintenance. At first the mathematical modeling of BLDC motor that is suitable to analyze the dynamic performance will be given.A method of torque hysteresis controller will be adapted to drive the motor such that the current (or torque) ripple can be restricted within the predefined band-gap. Moreover, a new current blocking strategy is proposed to prevent the current drained from DC supply when the torque demand is set to zero, that can prolong the capacity voltage of batteries. Some simulation results were carried out using MATLAB/Simulink to verify the proper modeling as well as functionality of the controller.